Аппроксимациониый метод в задачах теории потенциала - Синайский, Е.С. (Український математичний журнал, 2000)
Досліджуються властивості апроксимаційиого методу В. К. Дзядика стосовно біноміальної функції. Вивчаються умови, за яких оцінка для відносної похибки наближення у рівномірній метриці є точною. Результати застосовуються до задач теорії потенціалу. We investigate the properties of the Dzyadyk approximation method in the case of a binomial function. We study conditions under which an estimate for the relative error of approximation in the uniform metric is exact. The results obtained are applied to certain problems in potential theory.